Development of assisted reproductive technologies for Mus spretus. Issue 1 (29th September 2020) - Hasegawa, Ayumi; Mochida, Keiji; Matoba, Shogo; Inoue, Kimiko; Hama, Daiki; Kadota, Masayo; Hiraiwa, Noriko; Yoshiki, Atsushi; Ogura, Atsuo
Abstract: The genus Mus consists of many species with high genetic diversity. However, only one species, Mus musculus (the laboratory mouse), is common in biomedical research. The unavailability of assisted reproductive technologies (ARTs) for other Mus species might be a major reason for their limited use in laboratories. Here, we devised ARTs for Mus spretus (the Algerian mouse), a commonly used wild-derived Mus species. We found that in vitro production of M. spretus embryos was difficult because of low efficacies of superovulation with equine chorionic gonadotropin or anti-inhibin serum (AIS) (5–8 oocytes per female) and a low fertilization rate following in vitro fertilization (IVF; 15.2%). The primary cause of this was the hardening of the zona pellucida but not the sperm's fertilizing ability, as revealed by reciprocal IVF with laboratory mice. The largest number of embryos (16 per female) were obtained when females were injected with AIS followed by human chorionic gonadotropin and estradiol injections 24 h later, and then by natural mating. These in vivo-derived 2-cell embryos could be vitrified/warmed with a high survival rate (94%) using an ethylene glycol-based solution. Importantly, more than 60% of such embryos developed into healthy offspring following interspecific embryo transfer into (C57BL/6 × C3H) F1 female mice. Thus, we have devised practical ARTs for Mus spretus mice, enabling efficient production of embryos and animals, with safe laboratory preservation of their strains. In addition, we have demonstrated that interspecific embryo transfer is possible in murine rodents. Abstract : Embryos from wild-derived Mus spretus mice can be efficiently produced, cryopreserved, and transferred into laboratory mouse females using newly developed assisted reproductive technology protocols.